2010
DOI: 10.1093/nar/gkq851
|View full text |Cite
|
Sign up to set email alerts
|

BSDB: the biomolecule stretching database

Abstract: We describe the Biomolecule Stretching Data Base that has been recently set up at http://www.ifpan.edu.pl/BSDB/. It provides information about mechanostability of proteins. Its core is based on simulations of stretching of 17 134 proteins within a structure-based model. The primary information is about the heights of the maximal force peaks, the force–displacement patterns, and the sequencing of the contact-rupturing events. We also summarize the possible types of the mechanical clamps, i.e. the motifs which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 44 publications
0
51
0
Order By: Relevance
“…A mechanical clamp is defined as a structural region in a protein that is responsible for the enhanced resistance to stretching. This element therefore confers mechanical robustness and provides the rate-limiting step for the unfolding of a protein [191][192][193]. In the case of the I27 protein [189], the force bearing region was identified as a cluster of six hydrogen bonds and, for the protein to unfold, simultaneous rupturing of these hydrogen bonds was required ( Figure 24B).…”
Section: Mechanical Clamps Motifs In Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…A mechanical clamp is defined as a structural region in a protein that is responsible for the enhanced resistance to stretching. This element therefore confers mechanical robustness and provides the rate-limiting step for the unfolding of a protein [191][192][193]. In the case of the I27 protein [189], the force bearing region was identified as a cluster of six hydrogen bonds and, for the protein to unfold, simultaneous rupturing of these hydrogen bonds was required ( Figure 24B).…”
Section: Mechanical Clamps Motifs In Proteinsmentioning
confidence: 99%
“…More recently, a simple elastic model has also been used to describe this general trend between unfolding force and type of secondary structure [197]. An extensive, systematic theoretical study of protein secondary structures from the PDB permitted the identification of a number of mechanical clamp motifs [192,193] (Figure 25). These motifs were defined according to the hydrogen bond arrangements between secondary structure elements within the protein, and have since been found to occur in many proteins across all branches of life.…”
Section: Mechanical Clamps Motifs In Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an early molecular dynamics study on the I27 protein identified a 'mechanical clamp' region within the secondary structure which involved two neighbouring betastrands 70 . Mechanical clamps have since been identified in many 75 other proteins 9, [71][72][73][74] . Further studies have examined side chain packing and long-range interactions in topologically similar proteins 52 , hydrophobic packing in the hydrophobic core of a protein 75 , solvent accessibility of hydrogen bonds 76 , non-native interactions 71 and bond patterns as well as the identification of 80 "strong" and "weak" sequence motifs in protein families 24,25,[76][77][78][79] .…”
Section: Single Molecule Force Spectroscopy To Study Proteinsmentioning
confidence: 99%
“…To address the questions above and to extend the diversity of a repository of building blocks for protein-based materials requires further studies of many proteins preferentially with extreme properties and topologies different to already examined 70 proteins. We hope that this recent survey of available data on mechanically studied proteins together with available databases of simulated protein stretching 73,90 will provide a useful overview to guide future studies in this exciting field of research. Table 1.…”
mentioning
confidence: 99%